(untitled) (Comparatismi, 2018)
By enlarging the concept of literariness to the concept of narrativity, it is possible to look at narrative genres instead than literary genres. Major changes in the creation of stories have always been depending on technical constraints: epic was the main poetic genre of orality, novel the main literary genre fostered by literacy, and TV series are the main audiovisual genre. TV series are composed by a superimposition of semiotic levels (images, sounds, and texts); accordingly, they require a competent audience that is committed to a united hermeneutic effort. Twin Peaks, the TV series created by David Lynch and Mark Frost, is a complex narrative enthusiastically analyzed by an active fan base on online forums.